Assembly and application of a synthetic bacterial community for enhancing barley tolerance to drought - Rigerte, Linda; Heintz-Buschart, Anna; Reitz, Thomas; Tarkka, Mika T. (Frontiers in Bacteriology, 2025)
Under climate change scenarios for temperate regions in Europe, prolonged droughts pose a major threat to barley production, but few studies have been conducted on stress mitigation strategies using plant-beneficial rhizobacteria. With this in mind, we isolated and screened a culture collection of drought-tolerant bacteria from the barley rhizosphere. From this collection, we assembled a 16-member consortium based on their relative abundances in the rhizosphere after drought and in vitro osmotic stress tolerance (Drought Tolerant Synthetic microbial Community/”DT-SynCom”). Members of the DT-SynCom range from Proteobacteria to Firmicutes and Actinobacteria. We used Oxford Nanopore and Illumina technologies to assemble complete genomes. Whole genome annotation revealed the presence of a number of genes associated with plant growth promoting traits such as IAA biosynthesis, ACC deaminase activity and siderophore production. In vitro assays confirmed auxin production, ACC deaminase activity, siderophore production, inorganic P solubilization, and cellulase and chitinase activities by the selected bacterial strains. The consortium members were not antagonistic to each other, and were either neutral or beneficial to barley shoot and root growth of barley when applied individually in vitro. To clarify the effect of the designed DT-SynCom on barley drought tolerance, a pot experiment was conducted under drought stress conditions. The DT-SynCom reduced the number of wilting leaves and had a positive effect on barley growth under drought. The results of the research suggest that the members of the barley DT-SynCom have beneficial plant growth promoting traits that result in improved plant growth under drought stress.